Awareness, Attitude, and Current Practices Toward Influenza Vaccination Among Physicians in India: A Multicenter, Cross-Sectional Study - Vora, Agam; Shaikh, Ashfaque (Frontiers in Public Health, 2021)
Background: Although annual influenza vaccination is recommended for healthcare providers (HCPs), vaccination rate among HCPs in India is generally low. This cross-sectional survey was conducted to evaluate physicians' awareness, attitude, and current practices towards influenza vaccination in high-risk groups in India. Methods: The survey was performed in June-July 2020, wherein consulting physicians, pulmonologists, diabetologists, obstetricians/gynaecologists, or cardiologists across 14 cities completed a 39-item questionnaire consisting of 3 sections, one each on awareness, attitude, and practice patterns. Descriptive statistics were used to summarize the study results. Statistical analysis was performed for comparison of subgroups by physician specialty, city of practice (metro/non-metro), and zone of practice (north/south/east/west). Level of statistical significance was set at p<0.05. Results: In all, 780 physicians completed the survey. Of these, 3.97%, 53.08%, and 42.95% had high, medium, and low level of awareness about influenza/influenza vaccination, respectively. Statistically significant (p<0.05) between-group differences were found by physician specialty and zone of practice. In terms of attitude towards vaccination of high-risk group subjects, only 0.9% physicians were “extremely concerned”, while the majority (92.56%) were “quite concerned” and 6.54% were a “little concerned, with no reported significant differences between different subgroups. With regard to practice patterns, 82.82% of physicians offered influenza vaccines to their patients, 32.69% vaccinated 10%-25% of patients per month, and 38.85% required and offered the vaccine to their office staff. Physicians’ reasons for not prescribing influenza vaccines to patients included fear of side effects (16.54%), cost (15.64%), lack of awareness about availability (15.38%), absence of belief that it is beneficial (14.36%), history of side effects (13.46%), and patients’ fear of needles (11.28%). Conclusion: These findings suggest the need to implement educational strategies among physicians to enhance their awareness about influenza vaccination and improve their attitudes and current practices towards influenza vaccination especially in high-risk groups in India.